The quality of maternal secure-base scripts predicts children's secure-base behavior at home in three sociocultural groups - Vaughn, Brian E. (2012)
The secure-base phenomenon is central to the Bowlby/Ainsworth theory of attachment and is also central to the assessment of attachment across the lifespan. The present study tested whether mothers’ knowledge about the secure-base phenomenon, as assessed using a recently designed wordlist prompt measure for eliciting attachment-relevant stories, would predict their children’s securebase behavior, as assessed by observers in the home and summarized with the Attachment Q-set (AQS). In each of three sociocultural groups (from Colombia, Portugal, and the US), scores characterizing the quality of maternal secure-base narratives elicited using the word-list prompt procedure were internally consistent, as indicated by tests of cross-story reliability, and they were positively and significantly associated with the child’s security score from the AQS for each subsample. The correlation in the combined sample was r(129) = .33, p < .001. Subsequent analyses with the combined sample evaluated the AQS item-correlates of the secure-base script score. These analyses showed that mothers whose stories indicate that they have access to and use a positive secure-base script in their story production have children who treat them as a “secure base” at home. These results suggest that a core feature of adult attachment models, in each of the three sociocultural groups studied, is access to a secure-base script. Additional results from the study indicate that cross-language translations of the maternal narratives can receive valid, reliable scores even when evaluated by non-native speakers.